The emergence of oropouche fever: A potential new threat? - Shriyansh Srivastava; Ranjit Sah; Molakpogu Ravindra Babu; Deepika Sharma; Dheeraj Sharma; Sachin Kumar; Sathvik Belagodu Sridhar; Tarun Wadhwa; Javedh Shareef; G.S.N. Koteswara Rao; Jack Feehan; Vasso Apostolopoulos; et al. (New Microbes and New Infections)
Oropouche fever, caused by the Oropouche virus (OROV), has become a significant public health concern. Recent outbreaks highlight its increasing global spread, driven by environmental, social, and ecological factors. The disease presents clinical similarities to other arboviral infections, making accurate diagnosis essential for effective management and prevention. This article examines the epidemiological patterns of Oropouche fever, including its geographic distribution and outbreak drivers. It explores the clinical manifestations of the disease, focusing on common symptoms, complications such as fatal cases and fetal abnormalities, and the necessity of differential diagnosis. The pathophysiology of OROV infection is analyzed, detailing viral entry mechanisms, immune responses, and the role of vectors in transmission. Additionally, we assess diagnostic challenges, comparing serological and molecular methods while identifying their limitations. Therapeutic strategies are also reviewed, including symptomatic treatments and potential antiviral candidates. Findings indicate that OROV infections mimic other arboviral diseases, complicating clinical diagnosis. Current diagnostic tools have limitations in accuracy and accessibility, particularly in resource-limited settings. Symptomatic treatment remains the primary approach, as no specific antiviral therapies or vaccines exist. The study identifies gaps in diagnostic development, vaccine research, and public health surveillance. Oropouche fever threatens global health, necessitating improved surveillance, diagnostic tools, and targeted research efforts. Enhancing epidemiological studies and developing effective vaccines will mitigate its impact. Strengthening public health strategies can help control the spread of OROV and reduce its burden on affected populations.